Exploring the Piezoelectric Properties of Bismuth Ferrite Thin Films Using Piezoelectric Force Microscopy: A Case Study - Misiurev, Denis; Kaspar, Pavel; Sobola, Dinara; Papež, Nikola; H Fawaeer, Saleh; Holcman, Vladimír (Materials (Basel, Switzerland), 2023)
Over recent decades, the scientific community has managed to make great progress in the theoretical investigation and practical characterization of bismuth ferrite thin films. However, there is still much work to be completed in the field of magnetic property analysis. Under a normal operational temperature, the ferroelectric properties of bismuth ferrite could overcome the magnetic properties due to the robustness of ferroelectric alignment. Therefore, investigation of the ferroelectric domain structure is crucial for functionality of any potential devices. This paper reports deposition and analyzation of bismuth ferrite thin films by Piezoresponse Force Microscopy (PFM) and XPS methods, aiming to provide a characterization of deposited thin films. In this paper, thin films of 100 nm thick bismuth ferrite material were prepared by pulsed laser deposition on multilayer substrates Pt/Ti(TiO2)/Si. Our main purpose for the PFM investigation in this paper is to determine which magnetic pattern will be observed on Pt/Ti/Si and Pt/TiO2/Si multilayer substrates under certain deposition parameters by utilizing the PLD method and using samples of a deposited thickness of 100 nm. It was also important to determine how strong the measured piezoelectric response will be, considering parameters mentioned previously. By establishing a clear understanding of how prepared thin films react on various biases, we have provided a foundation for future research involving the formation of piezoelectric grains, thickness-dependent domain wall formations, and the effect of the substrate topology on the magnetic properties of bismuth ferrite films.
Keywords: PLD; XPS; PFM; bismuth ferrite; thin film; AFM; nanomaterials; ferroelectric; multiferroic